Pengaruh E-Service Quality dan Persepsi Harga terhadap Brand Loyalty : Survei pada Reseller Mukena Arrinda Collection - Radhita Bella Tri Pratiwi (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of E-Service Quality and Price Perception on Brand Loyalty (Survey on Reseller Mukena Arrinda Collection). The method used in this study is causality through a survey approach. With a research sample of 85 Reseller Mukena Arrinda Collection. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that E-Service Quality and Price Perception had a significant influence on Brand Loyalty at Reseller Mukena Arrinda Collection. Partially E-Service Quality has a significant influence on Brand Loyalty in Reseller Mukena Arrinda Collection. Price Perception has a significant influence on Brand Loyalty in Reseller Mukena Arrinda Collection.